Thermal Behavior of Some Bent-Core Resorcinol Derivatives with Azo-Type Spacers and Variable Flexible Chain - Ionica Ciobanu, Catalina; Drochioiu, Gabi; Carlescu, Irina; Lisa, Gabi; Antoci, Vasilichia; Vasilache, Violeta; Scutaru, Dan (Letters in Organic Chemistry, 2016)
Background: This paper investigates the thermal behavior of some synthesized bentshaped compounds with liquid crystalline properties. The newly synthesized resorcinol-based compounds contain five benzene-rings connected by azo bond type and ester linkage. Methods: The thermal stability studies were performed under dynamic conditions of temperature, by applying thermogravimetry, derivative thermogravimetry and differential thermal analysis, the same operational parameters being used in order to obtain comparable results. Results: Compounds with shorter chain length presented liquid crystalline properties, as they were evidenced by polarizing optical microscopy (POM) and differential scanning calorimetry (DSC). Conclusion: The length of terminal flexible chains was related to various temperatures of thermal degradation and was shown to influence favorably the thermal stability of bent core resorcinol derivatives.
Keywords: bent-shaped compounds